PRINCIPLES OF LEAN MANAGEMENT IN OPTIMIZATION OF PRODUCTION PROCESSES (Marketing Journal, 2025)
This article analyzes the theoretical and practical aspects of applying Lean Management principles in optimizing production processes. The study highlights the significance of the Lean concept in improving production efficiency, rational use of resources, and minimizing waste. Special attention is given to the implementation of Lean approaches in Uzbekistanʼs industrial enterprises, the development of Kaizen culture, and the integration of digital technologies into manufacturing systems. The results show th at Lean Management serves as a key factor in enhancing industrial competitiveness and achieving sustainable development.
Keywords: Lean management; production optimization; Kaizen; efficiency; resource saving; sustainable development; Uzbekistan industry. № 10-SON OKTA BR; 2025 -YIL 474